PENDAMPINGAN PERHITUNGAN BREAK EVEN POINT (BEP) PADA BADAN USAHA MILIK DESA (BUMDes) HARAPAN KITA, WADUK KARIAN, DESA PASIR TANJUNG, RANGKASBITUNG, LEBAK-BANTEN.: PENDAMPINGAN PERHITUNGAN BREAK EVEN POINT (BEP) PADA BADAN USAHA MILIK DESA (BUMDes) HARAPAN KITA, WADUK KARIAN, DESA PASIR TANJUNG, RANGKASBITUNG, LEBAK-BANTEN. - Dewi, Susana; Maesaroh; Firmansyah; Purnama, Sri Intan; Harismasakti, Eris; Juminawati , Sri; Sumarno, Dodi Iwan (Jurnal Abdimas Universitas Insan Pembangunan Indonesia, 2025)
Break Even Point (BEP) is a condition where a company experiences a position of neither profit nor loss or experiences a break-even point. This study aims to provide assistance in calculating the Break Even Point at the Harapan Kita, which operates in boat rental and public toilet services. The problem faced by Harapan Kita BUMDes is that it has not yet carried out a comprehensive or detailed BEP calculation, while the BEP calculation is very important for a company to use to determine the break-even point of this business. With this assistance, it is hoped that it can help the company in overcoming this problem. In this assistance, the author uses a mathematical method in analyzing the BEP which is used as a basis for consideration in making profit planning for the next period. The conclusion of the results of this mentoring activity is that it is important to have a report from this mentoring activity because the mentoring partners do not fully understand the calculation of the BEP, therefore BUMDes Harapan Kita needs to carry out a comprehensive BEP calculation to find out the break-even point during the business process. Many things and experiences that the author received, one of which is the importance of establishing good communication relationships, discipline, responsibility and cooperation between teams and can adapt to the method, it is hoped that they can practice it so that in the future the business being run can develop better and be more advanced than before.